APLICAÇÃO DE MICROFILTRAÇÃO E ULTRAFILTRAÇÃO COMO PÓS-TRATAMENTO DE EFLUENTE DE LODO ATIVADO EM UMA INDÚSTRIA DE PAPEL E CELULOSE - Neves, Ludmila Carvalho (2014)
This study evaluated and compared the application of membranes filters micro and ultrafiltration as alternative post- treatment of effluent from a pulp and paper industry. Filtration tests were performed, on a laboratory scale, in pilot equipment for micro and ultrafiltration. To optimize the treatment employed, the first step of this research was aimed at determining the optimal operating conditions of flow velocity, pressure operation and backwash interval for each tested membrane. Subsequently, we evaluated the performance of micro and ultrafiltration membranes with regard to removal efficiencies of color, COD, turbidity, ABS254, lignin/tannin and total solids as well as with respect to permeate flux obtained. After the tests the membranes were subjected to the process of chemical cleaning with hypochlorite solution. During the experiments it was found that the cake formation on the surface of the membranes was the major fouling mechanism. The results indicated that the micro and ultrafiltration membranes have improved effluent quality, with 84% removal efficiency of color employing the UF and 75% with the MF, 84.3 % of COD for UF and 80 % for MF, 99 % of turbidity for both treatments, still, the UF has removed 82.5 % of the lignin and the MF has removed 76.5 %, for the ABS254 there was a decrease of 73.6 % for UF and 56.4 % for MF. Thus the treatments used showed great potential as an alternative of post-treatment of effluent from the pulp and paper industry studied. The values of hydraulic permeability obtained in step chemical cleaning of the membranes revealed that the chemical cleaning was effective.